Brand Valuation: Financial - Marketing Interface of Metrics - Uzma, Shigufta Hena; Kumar, Naveen (Indian Journal of Marketing, 2010)
The international accounting standards have given brand assets recognition as an intangible asset separating itself from goodwill, though, the U.S. GAAP and the IAS do not recognize internally generated brands as assets (FRS 142, IAS 38). However, if it fulfills these criteria as "identifiable", "controllable" and "liable" to have "future economic benefits" over its "useful life", then it would be recognized as an intangible asset. The controversy that surrounds accounting professions is that though a brand meets the above mentioned criteria, it has so far not been accounted for separately in the balance sheet (Cravens and Guilding, 1999; Mather and Peasnell 1991). Numerous empirical studies have been conducted by financial accounting and marketing researchers to determine approaches of brand valuation. The scope of manipulation and ambiguity draws the reluctance of financial standards to include brand asset valuation on the balance sheet. The biggest challenge comes with regard to the companies accepting the best alternative way for recognizing and accounting intangible assets as "brand". For the last two decades, concepts from the marketing perspective have come up as brand equity (Aaker, 1996) and linking it with customer based brand equity (Keller, 1993). Different dimensions have been considered in measuring brand, and an eventual growth from the term "brand" to "brand equity" has also been incorporated, extending the scope of brand valuation to different measurement metrics. The researchers have again opened up the debate of placing brand assets on the balance sheet (Yeung and Ramasamy, 2007; Keller and Lehmann, 2006). Yeung and Ramasamy, (2007) tried to establish a relation of brand value with firm performance in their study of 50 US companies. They presented that the brand equity and the performance of the firm in the stock market have a strong link. The value relevance of this information and its usefulness would prove successful to place it in the balance sheet. The objective of the first section of the paper is to draw the background for accounting for brands. The second section of the paper is to review the existing approaches for accounting brand from both financial-marketing and marketing perspective and their measurement metrics that can be used in brand valuation the last section deals with discussion and further research to be undertaken.